Positive electrode active material, positive electrode, lithium ion battery, and method for producing positive electrode active material
By using lithium nickel composite oxide powder with controlled particle size and resistance ratios, and crushing it in an inert gas atmosphere, the balance between increased reaction area and reduced resistance is achieved, improving lithium ion battery performance.
Patent Information
- Application Number
- JP2022123406
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-02
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-08-02
AI Technical Summary
Lithium ion batteries face increased resistance due to the generation of nascent surfaces when the positive electrode active material is crushed, which counteracts the intended reduction in resistance from increased specific surface area.
The positive electrode active material is composed of lithium nickel composite oxide powder with specific particle size and resistance component ratios, crushed in an inert gas atmosphere to maintain a balance between increased reaction area and reduced resistance components.
This approach effectively reduces battery resistance by optimizing the particle size and resistance component generation, enhancing the battery's performance.
Smart Images

Figure 0007619339000005 
Figure 0007619339000006 
Figure 0007619339000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material, a positive electrode, a lithium ion battery, and a method for producing a positive electrode active material. [Background technology]
[0002] Japanese Patent Laid-Open Publication No. 2011-116580 (Patent Document 1) discloses a nickel-cobalt-manganese composite hydroxide having a small particle size and a uniform particle size distribution. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-116580 A Summary of the Invention [Problem to be solved by the invention]
[0004] There is a demand for lowering the resistance of lithium ion batteries (hereinafter, may be abbreviated as "batteries"). For example, the specific surface area of the positive electrode active material may be increased by crushing the positive electrode active material. The increase in the specific surface area may increase the reaction area. This is expected to reduce the resistance.
[0005] However, new surfaces may be generated by crushing the positive electrode active material. The new surfaces are active. Resistance components may be generated by reactions on the new surfaces. An increase in the resistance components may actually increase the resistance.
[0006] The present disclosure is directed to reducing drag. [Means for solving the problem]
[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0008] 1. The positive electrode active material contains lithium nickel composite oxide powder. The positive electrode active material exhibits the relationship represented by the following formulas (1) and (2). 0.1≦d×R×R≦0.4 … (1) d≦2.7 …(2) In the above formulas (1) and (2), d has a unit of μm. d indicates the D50 of the lithium nickel composite oxide powder. R is a dimensionless quantity. R indicates the ratio of the height of the second peak to the height of the first peak in the oxygen absorption spectrum by XAFS measurement. The first peak has a peak top in the range of 529 to 530 eV. The second peak has a peak top in the range of 533 to 534 eV.
[0009] In the above formula (1), "d × R × R (hereinafter referred to as "dR 2 " also written as "D50"".)" includes information on particle size and information on the amount of generated resistance component. According to the new findings of the present disclosure, when D50 is 2.7 μm or less and dR 2 When is between 0.1 and 0.4, a reduction in resistance is expected. This is thought to be because the drag-reducing effect due to the increase in reaction area exceeds the drag-increasing effect due to the generation of resistance components.
[0010] 2. The positive electrode active material described in the above item "1" may further satisfy the relationship of the following formula (3). 0.32≦R≦0.49 …(3)
[0011] By satisfying the relationship of the above formula (3), a reduction in resistance is expected.
[0012] 3. In the positive electrode active material according to the above item "1" or "2", the ratio of the substance amount of Ni to the total substance amount of atoms other than Li and oxygen in the lithium nickel composite oxide powder may be 0.5 or more.
[0013] Hereinafter, "lithium nickel composite oxide" may be abbreviated as "LNO". Furthermore, "the ratio of the amount of substance of Ni to the total amount of substances of atoms other than Li and oxygen in the LNO powder" may be abbreviated as "Ni ratio". LNO with a Ni ratio of 0.5 or more is also called "high nickel material". High nickel materials tend to have high capacity. On the other hand, when high nickel materials are crushed, resistance components tend to be generated easily. In particular, for high nickel materials, it may be important to satisfy the relationship between the above formulas (1) and (2).
[0014] 4. In the positive electrode active material according to any one of the above items "1" to "3," the lithium nickel composite oxide powder may have a composition represented by the following formula (4). Li (1+x) Ni y Co z Mn (1-y-z) M a O (2-b) C b …(4) In the above formula (4), x, y, z, a, and b satisfy the relationships 0≦x≦0.7, 0.5≦y≦0.8, 0.1≦z≦0.2, 0≦a≦0.1, and 0≦b≦0.5. M is at least one selected from the group consisting of Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Si, Sn, Al, and Ag. C is at least one selected from the group consisting of F, Cl, and Br.
[0015] The LNO may further include additional atoms in addition to Ni, such as Co, Mn, etc.
[0016] 5. The positive electrode contains the positive electrode active material described in any one of the above items "1" to "4".
[0017] 6. The lithium ion battery comprises the positive electrode described in "5" above.
[0018] 7. A method for producing a positive electrode active material includes the following (a) and (b): (a) A lithium nickel composite oxide powder is prepared. (b) The lithium nickel composite oxide powder is crushed in an inert gas atmosphere to produce a positive electrode active material.
[0019] Oxygen and carbon dioxide in the crushing atmosphere are the resistive components (e.g., Li 2 CO 3 It is believed that this promotes the generation of oxidative stress (e.g., oxidative stress, oxidative stress, etc.). By disintegrating the LNO powder under an inert gas atmosphere, the relationship between the above formulas (1) and (2) tends to be satisfied. This is believed to be because the LNO can be disintegrated while reducing the generation of resistance components.
[0020] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is an example of the absorption spectrum of oxygen. [Diagram 2] FIG. 2 is a schematic flow chart of the method for producing the positive electrode active material in this embodiment. [Diagram 3] FIG. 3 is a conceptual diagram of a lithium ion battery in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] <Terms and definitions> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0023] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0024] For example, a numerical range such as "m to n%" includes an upper limit and a lower limit. That is, "m to n%" indicates a numerical range of "m% or more and n% or less." Furthermore, "m% or more and n% or less" includes "more than m% and less than n%." Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0025] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed in sequence.
[0026] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0027] If the compound has a stoichiometric formula (e.g., LiCoO 2 When a stoichiometric formula is expressed by a formula such as "LiCoO ", the stoichiometric formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, lithium cobalt oxide may be expressed by a formula such as "LiCoO 2 ", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping or substitution with trace elements may also be permitted.
[0028] "D50" refers to the particle size at which the cumulative frequency of the smaller particle size reaches 50% in the volume-based particle size distribution. The particle size distribution can be measured by a laser diffraction particle size distribution measuring device. The measurement sample can be prepared by dispersing the powder in water by ultrasonic treatment.
[0029] "Specific surface area" refers to the surface area per unit mass. The specific surface area can be derived from an adsorption isotherm by the BET single point method. The adsorption isotherm is measured by a gas adsorption amount measuring device.
[0030] <XAFS Measurement> R in the above formula (1) is determined by XAFS (X-ray Absorption Fine Structure) measurement. Examples of facilities that can perform XAFS measurement include the beamline "BL1N2" at the "Aichi Synchrotron Light Center."
[0031] A sample is prepared by holding a positive electrode active material (powder) on a substrate. For example, a positive electrode (electrode) containing the positive electrode active material may be used as the sample. The absorption spectrum of oxygen (O) is measured in the soft X-ray region of 500 to 580 eV by the TEY (Total Electron Yield) method.
[0032] FIG. 1 is an example of an absorption spectrum of oxygen. The first peak p1 has a peak top in the range of 529 to 530 eV. It is considered that the first peak p1 is derived from oxygen in LNO. The second peak p2 has a peak top in the range of 533 to 534 eV. It is considered that the second peak p2 is derived from oxygen in the resistance component. The resistance component is, for example, Li 2 CO 3 The spectrum is normalized by the XAFS analysis software "Athena." In the normalized spectrum, the ratio of the height of the second peak p2 to the height of the first peak p1 is calculated. This peak height ratio is "R."
[0033] <Cathode active material> The positive electrode active material contains LNO powder. The LNO powder is an aggregate of LNO particles. The positive electrode active material satisfies the relationships of the following formulas (1) and (2). 0.1≦dR 2 ≦0.4 …(1) d≦2.7 …(2)
[0034] By satisfying the relationship between the above formulas (1) and (2), it is expected that the resistance will be reduced. 2 may be, for example, 0.16 or more, 0.17 or more, or 0.20 or more. 2 may be, for example, 0.38 or less, 0.28 or less, or 0.27 or less.
[0035] The positive electrode active material may further satisfy, for example, the relationship of the following formula (3). 0.32≦R≦0.49 …(3) By satisfying the relationship of the above formula (3), a reduction in resistance is expected. R may be, for example, 0.33 or more, or 0.38 or more. R may be, for example, 0.45 or less.
[0036] The D50 of the LNO powder may be, for example, 1.7 μm or less, 1.6 μm or less, 1.5 μm or less, 1.4 μm or less, or 1.2 μm or less. The D50 of the LNO powder may be, for example, 1.0 μm or more. That is, d may satisfy the relationship of, for example, 1≦d≦1.7, 1≦d≦1.6, 1≦d≦1.5, 1≦d≦1.4, or 1≦d≦1.2.
[0037] The width of the particle size distribution of the LNO powder may be, for example, 0.1 to 10 μm. That is, the minimum value (Dmin) may be 0.1 μm and the maximum value (Dmax) may be 10 μm. The width of the particle size distribution may be, for example, 0.2 to 4 μm.
[0038] The specific surface area of LNO powder is, for example, 1.2 m 2 / g or more, 1.4m 2 / g or more, 1.7m 2 / g or more, or 2.1m 2 The specific surface area of the LNO powder may be, for example, 2.5 m 2 / g or less.
[0039] LNO causes a positive electrode reaction. LNO may have any crystal structure. LNO may have, for example, a layered rock salt structure. LNO includes Li, Ni, and O. LNO may consist of Li, Ni, and O. LNO is a host-guest system. Ni and O may form a host structure. Li behaves as a guest. The host structure may contain additional atoms in addition to Ni and O. The host structure may contain, for example, at least one selected from the group consisting of Co, Mn, and Al. The Ni ratio of LNO may be, for example, 0.5 or more. When the Ni ratio is 0.5 or more, strict atmosphere control may be required, for example, in the crushing process, in order to satisfy the relationship of the above formulas (1) and (2). The Ni ratio may be, for example, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more.
[0040] LNO may have a composition represented by the following formula (4), for example. Li (1+x) Ni y Co z Mn (1-y-z) M a O (2-b) C b …(4) In the above formula (4), x, y, z, a, and b satisfy the relationships 0≦x≦0.7, 0.5≦y≦0.8, 0.1≦z≦0.2, 0≦a≦0.1, and 0≦b≦0.5. M is at least one selected from the group consisting of Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Si, Sn, Al, and Ag. C is at least one selected from the group consisting of F, Cl, and Br.
[0041] In the above formula (4), y may satisfy, for example, 0.5≦y≦0.6, 0.6≦y≦0.7, or 0.7≦y≦0.8.
[0042] Generally, in the LNO powder, each LNO particle may be a secondary particle formed by agglomeration of a large amount of primary particles. The secondary particles may usually contain 100 or more primary particles. The LNO powder in this embodiment is crushed. The secondary particles after crushing are composed of a relatively small amount of primary particles. The LNO powder may be crushed to the primary particle level. The secondary particles after crushing may be composed of, for example, 30 or less, 20 or less, 10 or less, 5 or less, or 3 or less primary particles. The primary particles may exist alone. The number of primary particles contained in the secondary particles can be measured in a SEM (Scanning Electron Microscope) image of the positive electrode active material (powder). In the SEM image, for example, when two primary particles overlap, the primary particle at the back cannot be confirmed. However, in this embodiment, the number that can be confirmed in the SEM image is considered to be the number of primary particles contained in the secondary particle.
[0043] The secondary particles and the primary particles can each independently have any shape, for example, spherical, ellipsoidal, flake-like, cylindrical, etc.
[0044] <Method of manufacturing positive electrode active material> 2 is a schematic flow chart of the method for producing a positive electrode active material in this embodiment. Hereinafter, the "method for producing a positive electrode active material in this embodiment" may be abbreviated as "this production method." This production method includes "(a) preparation of LNO powder" and "(b) crushing."
[0045] (a) Preparation of LNO powder The manufacturing method includes preparing an LNO powder. The LNO powder may be prepared by any method. For example, the LNO powder may be synthesized by a coprecipitation method. For example, the LNO powder may be synthesized by the following procedure.
[0046] A sulfate such as Ni is prepared. An acidic aqueous solution is formed by dissolving the sulfate in water. For example, an acidic aqueous solution can be formed by dissolving nickel sulfate, cobalt sulfate, and manganese sulfate in water. For example, a neutralization reaction can occur by dropping an alkaline aqueous solution into the acidic aqueous solution. The alkaline aqueous solution may contain, for example, an aqueous NaOH solution and aqueous ammonia. A precipitate can be formed by the neutralization reaction. The precipitate is considered to contain a composite hydroxide (precursor). A dried product is formed by washing the precipitate and drying it. A mixture is formed by mixing the dried product with a lithium compound. The lithium compound is, for example, Li 2 CO 3 , LiOH, etc. The mixture is subjected to a heat treatment. The heat treatment may also be called "calcination". The heat treatment temperature may be, for example, 500 to 1000°C. The heat treatment time may be, for example, 5 to 30 hours. In this manner, LNO powder is synthesized.
[0047] 《(b) Disintegration》 This manufacturing method includes crushing the LNO powder under an inert gas atmosphere. By carrying out the crushing process under an inert gas atmosphere, a positive electrode active material that satisfies the relationship between the above formulas (1) and (2) tends to be produced. In this manufacturing method, a dry crushing device can be used. For example, a dry jet mill or the like may be used. The inert gas atmosphere may contain, for example, nitrogen, argon, helium, neon, or the like. The oxygen concentration and carbon dioxide concentration in the inert gas atmosphere are reduced as much as possible.
[0048] After the LNO powder is crushed, for example, classification, sizing, etc. may be further performed. For example, an airflow classifier may be used. The classification, etc. may also be performed in an inert gas atmosphere. By performing the classification, etc. in an inert gas atmosphere, it is expected that the resistance components will be reduced.
[0049] <Lithium-ion battery> FIG. 3 is a conceptual diagram of a lithium ion battery in this embodiment. Hereinafter, the "lithium ion battery in this embodiment" may be abbreviated as "this battery." This battery 100 may be a liquid battery, a polymer battery, or an all-solid-state battery. That is, this battery 100 may contain a liquid electrolyte (electrolytic solution), a gel electrolyte, or a solid electrolyte.
[0050] The battery 100 may include an exterior body (not shown). The exterior body may house the power generating element 150. The exterior body may have any shape. The exterior body may be, for example, a pouch made of a metal foil laminate film, or a case made of metal. The case may be, for example, cylindrical or rectangular.
[0051] The battery 100 includes a power generating element 150. The power generating element 150 includes a positive electrode 110, a separator 130, a negative electrode 120, and an electrolyte (not shown). The power generating element 150 may also be referred to as an electrode body, an electrode group, or the like. The power generating element 150 may be, for example, a layered type or a wound type.
[0052] 《Positive electrode》 The positive electrode 110 may be, for example, in the form of a sheet. The positive electrode 110 may include, for example, a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector may include, for example, an Al foil or the like. The positive electrode active material layer may be disposed on a surface of the positive electrode current collector. The positive electrode active material layer includes the above-mentioned positive electrode active material. As long as the positive electrode 110 includes the above-mentioned positive electrode active material, the positive electrode 110 may include an additional positive electrode active material. For example, the positive electrode active material layer may include LiFePO 4 The positive electrode active material layer may further include, in addition to the positive electrode active material, a conductive material, a binder, etc. The positive electrode active material layer may further include, for example, acetylene black (AB), polyvinylidene fluoride (PVDF), etc.
[0053] 《Negative electrode》 The negative electrode 120 may be, for example, sheet-shaped. The negative electrode 120 may include, for example, a negative electrode current collector and a negative electrode active material layer. The negative electrode current collector may include, for example, a Cu foil or the like. The negative electrode active material layer may be disposed on the surface of the negative electrode current collector. The negative electrode active material layer contains a negative electrode active material. The negative electrode active material may be in powder form or sheet form. The negative electrode active material may be, for example, natural graphite, artificial graphite, soft carbon, hard carbon, Si, SiO x (0 < x < 2), Si-based alloy, Sn, SnO x (0 < x < 2), Li, Li-based alloy, and Li 4 Ti 5 O 12 and may contain at least one selected from the group consisting of. The negative electrode active material layer may further contain a conductive material, a binder, etc. The negative electrode active material layer may contain, for example, vapor-grown carbon fiber (VGCF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), etc.
[0054] 《Separator》 The separator 130 is interposed between the positive electrode 110 and the negative electrode 120. The separator 130 separates the positive electrode 110 from the negative electrode 120. In the case of a liquid-based battery, the separator 130 may include, for example, a resin-made porous sheet or the like. In the case of an all-solid-state battery, the separator 130 may include, for example, a solid electrolyte layer or the like.
[0055] 《Electrolyte》 The electrolyte can form an ion conduction path. The liquid electrolyte includes, for example, a lithium salt and a solvent. The lithium salt may include, for example, LiPF 6 etc. The solvent may include, for example, ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), etc. The solid electrolyte may include, for example, sulfides (Li 3 PS 4 etc.).
Examples
[0056] <Preparation of Samples> Positive electrode active materials No. 1 to 14 were produced as follows (see Table 1 below). Hereinafter, for example, "positive electrode active material No. 1" may be abbreviated as "No. 1".
[0057] No.1 LNO powder (LiNi 0.5 Co 0.2 Mn 0.3 O 2 The LNO powder was used as the positive electrode active material without being crushed.
[0058] No.2~4 The No. 1 LNO powder was crushed in an air atmosphere using a dry jet mill. The wind pressure of the dry jet mill was 0.6 MPa. After crushing, the LNO powder was classified in an air flow classifier in an air atmosphere. The classification removed coarse powder and fine powder. The positive electrode active material was produced as described above.
[0059] No.5 LNO powder (LiNi 0.6 Co 0.2 Mn 0.2 O 2 The LNO powder was crushed and classified in an air atmosphere to produce a positive electrode active material.
[0060] No.6 LNO powder (LiNi 0.8 Co 0.1 Mn 0.1 O 2 The LNO powder was crushed and classified in an air atmosphere to produce a positive electrode active material.
[0061] No.7 LNO powder (LiNi 0.5 Co 0.2 Mn 0.3 O 2 ) was prepared. The LNO powder contained porous particles. The LNO powder was used as the positive electrode active material without being crushed.
[0062] No.8~11 The No. 1 LNO powder was crushed and classified in an inert gas atmosphere (nitrogen atmosphere) to produce a positive electrode active material.
[0063] No.12 The No. 5 LNO powder was crushed and classified under a nitrogen atmosphere to produce a positive electrode active material.
[0064] No.13 The No. 6 LNO powder was crushed and classified under a nitrogen atmosphere to produce a positive electrode active material.
[0065] No.14 The No. 10 LNO powder (which had been subjected to crushing and classification) was washed with water and dried to produce a positive electrode active material.
[0066] <Evaluation> The particle size distribution and specific surface area of each sample were measured. XAFS measurements were performed on each sample to identify the peak height ratio (R). The results are shown in Tables 1 to 4 below. In Tables 1 to 4 below, "Y" in the "Formula (1)" section indicates that the relationship in formula (1) is satisfied. "N" indicates that the relationship in formula (1) is not satisfied. The same applies to the "Formula (2)" section.
[0067] Test batteries for evaluation were prepared. The test battery configuration was as follows:
[0068] positive electrode Positive electrode active material: Samples obtained above (No. 1 to 14) Conductive material: AB Binder: PVDF
[0069] negative electrode Negative electrode active material: natural graphite Binder: CMC, SBR
[0070] Separator: Porous sheet (thickness 24 μm) Electrolyte: Electrolyte [LiPF 6 (1mol / L), EC+DMC+EMC]
[0071] The voltage of the evaluation battery was adjusted to 3.7 V. AC impedance measurements were performed in a thermostatic chamber set at -10°C. Charge transfer resistance (Rct) was calculated from the size of the arc appearing in the Cole-Cole plot. Rct in Tables 1 to 4 below is a relative value with the Rct of No. 1 being "1.00".
[0072] <Results and Discussion>
[0073] [Table 1]
[0074] [Table 2]
[0075] In Table 2 above, when the relationships of the above formulas (1) and (2) are satisfied, there is a tendency for the resistance to decrease.
[0076] Nos. 2 to 4 tend to have high resistance. In Nos. 2 to 4, the crushing process is carried out in an air atmosphere. Since a large amount of resistance components are generated, dR 2 is considered to be greater than 0.4.
[0077] Nos. 9 to 11 tend to have relatively low resistance compared to Nos. 2 to 4. In Nos. 9 to 11, the crushing process is carried out under an inert gas atmosphere. The generation of resistance components is suppressed, and the dR 2 is considered to be below 0.4.
[0078] No. 14 has high resistance. In No. 14, after crushing in an inert gas atmosphere, water washing is performed. The resistance components are reduced by the water washing, so dR 2 It is considered that the resistance is less than 0.1. However, it is considered that the water washing process inactivates part of the reaction surface, which increases the resistance.
[0079] [Table 3]
[0080] In Table 3 above, when the Ni ratio of LNO is 0.5 or more, the drag reduction effect is shown to be independent of the Ni ratio.
[0081] [Table 4]
[0082] In No. 7 in Table 4, the reaction area is increased not by crushing the secondary particles, but by making the secondary particles porous. No. 7 has a relatively large D50 and a specific surface area similar to that of No. 10 (crushed powder). However, No. 7 has a higher resistance than No. 10. The internal surface of the porous particles is not exposed to the outside, so it is thought that it is difficult for it to function as an effective reaction surface. The dR of No. 7 2 is greater than 0.4. [Explanation of symbols]
[0083] 100 battery, 110 positive electrode, 120 negative electrode, 130 separator, 150 power generating element, p1 first peak, p2 second peak.
Claims
1. Lithium nickel composite oxide powder, The lithium nickel composite oxide powder contains Li, Ni, and oxygen as essential components, and may contain at least one selected from the group consisting of Co, Mn, Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Si, Sn, Al, and Ag as an optional component; In the lithium nickel composite oxide powder, the ratio of the amount of Ni to the total amount of atoms other than Li and oxygen is 0.5 or more; Formula (1) and Formula (2): 0.1≦d×R×R≦0.4 (1) d≦2.7 ... (2) Fulfilling the relationship, In the formula (1) and the formula (2), d has a unit of μm and represents D50 of the lithium nickel composite oxide powder, R is a dimensionless quantity and indicates the ratio of the height of the second peak to the height of the first peak in the oxygen absorption spectrum measured by XAFS, The first peak has a peak top in the range of 529 to 530 eV, The second peak has a peak top in the range of 533 to 534 eV. Cathode active material.
2. Formula (3): 0.32≦R≦0.49 ... (3) Further satisfying the relationship of The positive electrode active material according to claim 1 .
3. The lithium nickel composite oxide powder has the formula (4): Li (1+x) Ni y Co z Mn (1-y-z) M a O (2-b) C b …(4) The composition is represented by In the formula (4), x, y, z, a, and b satisfy the relationships: 0≦x≦0.7, 0.5≦y≦0.8, 0.1≦z≦0.2, 0≦a≦0.1, and 0≦b≦0.5; M is at least one selected from the group consisting of Zr, Mo, W, Mg, Ca, Na, Fe, Cr, Zn, Si, Sn, Al, and Ag; C is at least one selected from the group consisting of F, Cl, and Br; The positive electrode active material according to claim 1 .
4. The positive electrode active material according to claim 1, Positive electrode.
5. The positive electrode according to claim 4, Lithium-ion battery.
6. A method for producing the positive electrode active material according to claim 1, comprising: (a) preparing a lithium nickel composite oxide powder; and (b) crushing the lithium nickel composite oxide powder under an inert gas atmosphere to produce the positive electrode active material; Including, A method for producing a positive electrode active material.
Citation Information
Patent Citations
Material for positive electrode of lithium secondary battery
JP2000285918A
Positive electrode active material for lithium secondary battery and its manufacturing method
JP2004327246A
Non-aqueous electrolyte secondary battery
JP2005251700A
Positive active material and nonaqueous electrolyte battery
JP2008010234A
Nickel-cobalt-manganese complex hydroxide particle and method of producing the same, positive electrode active material for nonaqueous electrolyte secondary battery and method of producing the same, and nonaqueous electrolyte secondary battery
JP2011116580A